2018
DOI: 10.1186/s12966-018-0756-3
|View full text |Cite|
|
Sign up to set email alerts
|

Longitudinal analysis of physical activity, sedentary behaviour and anthropometric measures from ages 6 to 11 years

Abstract: Background/ObjectivesThe aim of this study was to examine the effect of physical activity (PA) and sedentary behaviour (SB) on body mass index (BMI) and fat mass index (FMI) in children over the course of five years and identify potential bi-directional associations.Subjects/MethodsData were drawn from the EU Childhood Obesity Project (CHOP). PA and SB were measured with the SenseWear Armband 2 at the ages of 6 (T1), 8 (T2) and 11 (T3) years. Height and weight were measured and BMI was calculated at each time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
38
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 45 publications
(51 reference statements)
9
38
0
Order By: Relevance
“…Past studies have validated the SenseWear Pro Armband at high intensity exercise with reasonable concordance from the gold standard technique of energy expenditure measurement, the doubly labeled water method (ICC = 0.80, technical error of measurement 112 kcal/d and ICC = 0.96, technical error of measurement 104 kcal/d, for the cited studies, respectively) [21,22]. Furthermore, these activity monitors were previously used in a small high-altitude study of twelve individuals summiting an unnamed peak in the Karakoram Mountains (6,170m), as well as in children and clinical populations [23][24][25][26]. The SenseWear Pro Armbands were in operating range, as they were in contact with the body and covered from polar conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Past studies have validated the SenseWear Pro Armband at high intensity exercise with reasonable concordance from the gold standard technique of energy expenditure measurement, the doubly labeled water method (ICC = 0.80, technical error of measurement 112 kcal/d and ICC = 0.96, technical error of measurement 104 kcal/d, for the cited studies, respectively) [21,22]. Furthermore, these activity monitors were previously used in a small high-altitude study of twelve individuals summiting an unnamed peak in the Karakoram Mountains (6,170m), as well as in children and clinical populations [23][24][25][26]. The SenseWear Pro Armbands were in operating range, as they were in contact with the body and covered from polar conditions.…”
Section: Methodsmentioning
confidence: 99%
“…However, only few longitudinal studies among German adolescents are available. Schwarzfischer et al reported the longitudinal development of PA and SB at three time points (2008, 2010, and 2013) and associations with BMI and body fat, however, Germany was only one of five European countries included in this study and the measurement of PA was not the study's main purpose [22]. Braig et al reported associations of PA and ST with self-esteem in 11−13 year old adolescents in a very selective sample in a small city in southern Germany [3].…”
Section: Introductionmentioning
confidence: 92%
“…Evidence from longitudinal studies shows a decline in physical activity and an increase in sedentary behaviour (SB) from childhood through adolescence [8,[16][17][18][19][20][21][22]. However, only few longitudinal studies among German adolescents are available.…”
Section: Introductionmentioning
confidence: 99%
“…The decline and disinterest in physical activity begins early in life and there are no pharmacological treatments for physical inactivity (141,165). School care and health care should focus on the identification and treatment of youth with muscle weakness and should recognize muscle strength as a biomarker of health.…”
Section: Commentarymentioning
confidence: 99%